Genetic markers indicate that hybrids of Pseudoplatystoma (Siluriformes, Pimelodidae) are reproducing in natural environments in southeastern Brazil - Freitas-Souza, Diogo [UNESP]; Nobile, André Batista [UNESP]; do Prado, Fernanda Dotti [UNESP]; Serrano, Érica Alves [UNESP]; Lima, Felipe Pontieri [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP]; Oliveira, Claudio [UNESP] (Springer Nature, 2022)
Due to the constant propagule pressure of invasive species, aquaculture is considered to be one of the principal mechanisms for the introduction of non-native fish species into wild habitats in Brazil. The ongoing expansion of fish farming in many inland areas is linked directly to the increase in the production of hybrids. Over the past decade, several records of the occurrence of hybrids have been obtained from wild environments, and several studies have shown that the introduction of non-native taxa has led to genetic introgression in some native species. In this context, the present study evaluated whether a population containing adult Pseudoplatystoma hybrids, on the Mogi-Guaçu River in the Upper Paraná Basin, southeastern Brazil, has been able to establish reproductive continuity, given that the genetic introgression recorded in the parent species indicates backcrossing in the local population. Initially, 59 fish eggs and larvae were identified as either Pseudoplatystoma corruscans or Pseudoplatystoma reticulatum based on a barcoding sequence of the Cytochrome c oxidase I gene. Using three diagnostic nuclear markers (the RAG2 and 18S gene, and the Prt36 microsatellite), four eggs and larvae (of the 40 sequenced) were identified as members of the parent species (either P. corruscans or P. reticulatum), whereas the other 36 samples were identified as hybrids. The hybrid genotypes indicate the occurrence of recent crosses between the species in the wild environment due to the presence of first generation (F1) hybrids. The fertility of the F1 hybrids was confirmed by the presence of eggs and larvae identified as advanced hybrids, probably either backcrosses or post-F1 hybrids. Hybridization has advanced at an alarming rate in the P. corruscans populations of the Mogi-Guaçu River, with the proportion of hybrid individuals increasing progressively over the years.
Keywords: Conservation areas; Genetic introgression; Ichthyoplankton; Upper Paraná River